Factors Affecting Timeliness of Financial Reporting in Banks Listed on the Indonesia Stock Exchange - Risky Amelia; Muryani Arsal; Chairul Ihsan Burhanuddin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of gearing ratio, profitability, company age, company size, and ownership structure on the timeliness of financial reporting in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Timeliness of financial reporting is very important because it can affect investor decision making and market perception of company performance. This study uses a quantitative approach with the logistic regression analysis method. The sample consisted of 23 banking companies selected based on purposive sampling techniques and met the criteria for three years of observation, resulting in 69 observations. The results of the study showed that simultaneously the five independent variables affected the timeliness of financial reporting with a contribution of 50.9%. Partially, gearing ratio, company age, and ownership structure were shown to have a significant effect, while profitability and company size did not show a significant effect. This finding implies that the aspects of leverage, company maturity, and transparency of public ownership play an important role in increasing compliance with timely financial reporting.